2010
DOI: 10.1186/1749-799x-5-53
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic splinting in wrist extension following distal radius fractures

Abstract: BackgroundWrist flexion contracture is a common pathology which presents secondary to distal radius fractures. Joint stability, restoration and early mobilization are frequently achieved through surgical treatment after such an injury. The purpose of this retrospective study was to evaluate the initial effect of dynamic splinting on wrist extension (active range of motion), in both surgical and non-surgical patients following distal radius fractures.Methods Records were obtained from 133 patients who were trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
14
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 21 publications
(23 reference statements)
2
14
0
Order By: Relevance
“…8 Moreover, evidence from previous studies on dynamic splinting show empirical efficacy in prolonged duration of stretching at end-range stretching. [9][10][11][12][13][14][15][16][17][18][19][20] More specifically, these benefits compare favorably with Lai, et al, who observed neurological patients with chronic contracture 14 , as well as the observations made in this case series.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…8 Moreover, evidence from previous studies on dynamic splinting show empirical efficacy in prolonged duration of stretching at end-range stretching. [9][10][11][12][13][14][15][16][17][18][19][20] More specifically, these benefits compare favorably with Lai, et al, who observed neurological patients with chronic contracture 14 , as well as the observations made in this case series.…”
Section: Discussionsupporting
confidence: 76%
“…Stretching protocols for contracture have been documented as effective in reduction and it is suggested that the total duration of time at end-range of motion is the integral variable for the greatest success. 8,9,11,12 Mosely, et al, tested passive stretching, but their total durations of stretching in the four week study were 2.8 hours (short duration group stretching 6 min/day) and 15 hours (long duration stretching 30 minutes per day). 2 This supports the evidence that "prolonged passive stretching" (6-8 continuous hours) is required for contracture reduction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations